Extending the technology acceptance model 3 to digital healthcare: exploring citizen adaptability to telemedicine across national cultures - Ribeiro, Tirsa Maria Carelsz (2024)
The rapid growth of digital technologies has transformed industries, with telemedicine becoming a key solution for remote healthcare delivery. While telemedicine offers benefits like enhanced accessibility and reduced travel time, its adaptation varies across cultural contexts. This dissertation explores how national culture influences adaptability to telemedicine by applying Hofstede’s cultural dimensions and the Technology Acceptance Model 3 (TAM3). The study focuses on how individuals who are already using telemedicine perceive its adaptation, comparing Brazil and the Netherlands—countries with distinct cultural traits. A survey of 112 respondents (54 from Brazil and 58 from the Netherlands) assessed perceptions of telemedicine. Key constructs from TAM3, such as perceived usefulness (PU), perceived ease of use (PEOU), and perceptions of external control, were evaluated. Structural equation modeling (SEM) was used to analyze relationships and test hypotheses. Findings reveal cultural differences in telemedicine adaptation. In the Netherlands, characterized by individualism and low power distance, perceived usefulness was strongly linked to telemedicine adaptation (r=0.735, p=0.00), with autonomy and convenience being highly valued. In Brazil, a collectivist society with higher power distance, the correlation between perceived usefulness and adaptation was weaker (r=0.093, p=0.44), with social factors like image playing a more significant role. Perceived ease of use was also higher in the Netherlands (r=0.907, p=0.00) compared to Brazil (r=0.214, p=0.02). External control, such as technical support, was more influential in Brazil (r=0.522, p=0.00) than in the Netherlands (r=-0.345, p=0.29). These results suggest that in individualistic, low power distance cultures like the Netherlands, telemedicine adaptation is driven by ease of use and autonomy. In collectivist, high power distance cultures like Brazil, social acceptance and external support are more crucial. The study underscores the need for culturally tailored telemedicine strategies for effective adaptation across diverse populations.